SEASONAL VARIATIONS IN CONCENTRATIONS OF TOXIC TRACE METALS IN DEEP-SEA FISH, IDENTIFIED WITH STAT-AAS AND ICP-AES - Yaman, Burak; Yaman, Mehmet (Polish Society Magnesium Research, 2017)
Monitoring toxic metal concentrations in fish is very important for human health because fish, which are consumed by humans, can accumulate toxic metals from water up to hazardous levels. The aim of this study has been to monitor the levels of Cd, Pb, Cu, Cr and Ni in three deep-sea fish species as well as to make a risk assessment of their consumption. The samples were digested in a microwave oven and the determinations were made by atomic absorption spectrophotometry (AAS) and inductively coupled plasma-atomic emission spectrophotometry (ICP-AES). The mean lead concentrations in the Salmo salar and Sarda sarda species were found to be 955 and 948 mu g kg(-1), respectively, and these levels are three-fold higher than the risk threshold level of 300 mu g kg(-1). Cd concentrations in only six samples were slightly higher than the maximum allowable concentrations (MACs) of 100 mu g kg(-1). Mean Cr and Ni concentrations in Salmo salar were found to be 866 and 472 mu g kg(-1), respectively, and these results were higher than in Sarda sarda (mean 388 mu g Cr kg(-1) and 356 mu g Ni kg(-1)) and Merlangius merlangus (mean 303 mu g Cr kg(-1) and 336 mu g Ni kg(-1)). The measured Pb concentrations in all muscles of Salmo salar and Sarda sarda were found to be significantly higher than the MAC values, while Cd in all studied samples was around or lower than the MACs. However, there is no carcinogenic risk for humans, and the risk of developing cancer over an average human lifespan is between 2.5 and 13 in 1,000,000.
Keywords: toxic metals; fish; atomic absorption; ICP-AES; risk assessment